Aeromedical retrievals in Queensland: A five‐year review. (6th July 2020) - Franklin, Richard C; King, Jemma C; Aitken, Peter J; Elcock, Mark S; Lawton, Luke; Robertson, Anita; Mazur, Stefan M; Edwards, Kristin; Leggat, Peter A
Abstract : A retrospective case series of aeromedical retrievals undertaken between 2010 and 2014 in the state of Queensland was undertaken. Key insights include the large proportion of retrievals for older adults, cardiology and injury‐related taskings. Aeromedical services play a vital role in enabling all sick and injured residents' have access to the level of care required irrespective of their location, or remoteness, of residence. Abstract: Objective: Aeromedical services are an essential part of the healthcare system. Centralised coordination of aeromedical retrieval tasking offers benefits for safety, timeliness and efficiency in service delivery. The aim of the present study is to review aeromedical retrievals in Queensland exploring patient demographics, temporal patterns and usage characteristics. Methods: This is a retrospective cases series for the period 1 January 2010 to 31 December 2014 incorporating data from Retrieval Services Queensland and Queensland Newborn Emergency Transport Service. Ethics approval was obtained (JCU‐HREC H6137 and Public Health Act #RD005673). Descriptive analysis of the de‐identified data was undertaken included patient demographics, referral and receiving locations, retrieval platform and acuity of transport request. Results: There were 73 042 aeromedical retrievals undertaken during the period, with an average of 40 cases per day (range 16–89). The majority (95%) of retrievals were for Queensland residents. Overall 23.1% of cases were cardiology‐related and 12.7% were injury‐related. Older adults aged 75–84 years had the highest rate of retrievals relative to the population with a crude rate of 942.4 per 100 000 per annum. Overall 14.9% of cases were Priority 1, which represents the tasking with the highest acuity but majority were Priority 4 (41.6%). One third (37.6%) of all patients were from inner regional locations. Conclusions: Potential investments in health service planning may alleviate the burden on aeromedical services, particularly related to cardiology services in inner and outer regional Queensland. Aeromedical services are pivotal in enabling all sick and injured residents' access to the highest quality of care regardless of the remoteness of their residence.